Industry 4.0 and its challenges / Rosliza Md Zani, Ramli Saad and Mohd Radzi Mohd Khir - Md Zani, Rosliza; Saad, Ramli; Mohd Khir, Mohd Radzi (Faculty of Business and Management, Universiti Teknologi MARA Cawangan Kedah, 2022)
There is no denying that technology plays a significantly important role in our daily lives; however, the increasingly linked culture we live in also has an impact on the business world. This is the point at which Industry 4.0 begins to take shape. Industrial Revolutions evolved with the first one in 1765. During Industrial Revolution 1, mechanization took place where there was a key discovery of the steam engine, which created a new source of energy which then helped accelerate the construction of railroad, thus developing the economy. In 1870, Industrial Revolution 2 arrived with an evolution of a new source of energy-gas, oil and electricity. The internal combustion engine was invented, as was the growth of steel demand, chemical synthesis, and communication systems such as the telegraph and telephone. The vehicle and the plane were also invented during the Industrial Revolution 2. In 1969, Industrial Revolution 3 began with the advancement of electronics, telecommunications, and computers. With new technologies, Industrial Revolution 3 paved the way for research, biotechnology and space exploration. Two key technologies were introduced; Programmable Logic Controllers (PLCs) and Robots, to facilitate the industrial sector (Institute of Entrepreneurship Development Team, 2019).